2019
DOI: 10.1029/2018jb017287
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Updated Paleointensity Database (QPI‐PINT) for 65–200 Ma: Implications for the Long‐Term History of Dipole Moment Through the Mesozoic

Abstract: The global paleointensity database for 65-200 Ma was analyzed using a modified suite of paleointensity quality criteria (Q PI ) such that the likely reliability of measurements is assessed objectively and as consistently as possible across the diverse data set. This interval was chosen because of dramatic extremes of geomagnetic polarity reversal frequency ranging from greater than 10 reversals per million years in the Jurassic hyperactivity period (155-171 Ma) to effectively zero during the Cretaceous Normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 88 publications
6
55
0
Order By: Relevance
“…This implies that, regardless of how frequently AD/NAD undergoes brief collapse, the field recovers to spend most of its time in a similarly dipole dominated state. Intervals of stable average AD dominance also apparently coincided with significant variations in long-term average field intensity [31][32][33] . This further suggests that the magnitude of the AD and NAD field are correlated on long-timescales such that the degree of AD dominance remains approximately constant.…”
Section: Resultsmentioning
confidence: 82%
“…This implies that, regardless of how frequently AD/NAD undergoes brief collapse, the field recovers to spend most of its time in a similarly dipole dominated state. Intervals of stable average AD dominance also apparently coincided with significant variations in long-term average field intensity [31][32][33] . This further suggests that the magnitude of the AD and NAD field are correlated on long-timescales such that the degree of AD dominance remains approximately constant.…”
Section: Resultsmentioning
confidence: 82%
“…This supports previous assertions that the time‐averaged field of the past 10 million years is not a perfect geocentric axial dipole but one with a more complex mean field morphology. Field strength compilations (e.g., Biggin et al., 2015; Bono et al., 2019; Kulakov et al., 2019; Hawkins et al., 2019; Shcherbakova et al., 2017; Smirnov et al., 2016) demonstrated that earlier times record different VDM distributions from the past 10 million years. It is suspected that for other intervals further back in geologic time, VGP dispersion and other estimates of PSV behavior are different than seen for this most recent interval (e.g., Biggin, Strik, et al., 2008; Biggin, van Hinsbergen, et al., 2008, 2009; de Oliveira et al., 2018; Doubrovine et al., 2019; Smirnov et al., 2011; Tarduno et al., 2002).…”
Section: Resultsmentioning
confidence: 99%
“…We then compared our API determinations with the subsets from Kulakov et al. (2019), which were analyzed using a suite of 10 paleointensity quality criteria (Q PI ). Subsets I‐III yield for the late Cretaceous interval (65–84 Ma) a median dipole strength around 34 ZAm 2 , that is, twice lower than our mean dipole strength of 58.9 ± 6.9 ZAm 2 derived from Tuoyun volcanics and baked sediments for the time interval 60–70 Ma.…”
Section: Discussionmentioning
confidence: 99%